Gambaran Implementasi Regulasi Kawasan Tanpa Rokok Dalam Upaya Menurunkan Prevalensi Perokok Di Kabupaten Blitar - Fitriani, Hari; Swadana, Nicholas Fransida; Artanti, Kurnia Dwi; Martini, Santi; Christanto, Daniel (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Blitar Regency already has a Regulation No. 1 of  2019 concerning Smoke-Freee Areas, carrying out technical capacity building for health workers in Stop Smoking Efforts (UBM) services. However, the number of smokers in Blitar Regency has not decreased, which is still 28.0%. This study aims to provide a descriptive description of the KTR regulations implemented by health facilities in Blitar Regency.  This is a type of quantitative research with a descriptive study with a cross-sectional design. The research material used was secondary data from KTR and Cigarette reports in Blitar Regency in 2022 for the PTM program. The number of smokers aged 10 - 18 years was 7678 people (4.47%) consisting of 81.61% male smokers and 18.39% female smokers. The number of schools that have implemented KTR is 894 (79.32%) and those that have not are 233 (20.68%). There are 3 clinics (12%) and 17 independent doctor practices (22.67%) that have implemented UBM. The results of the multiple linear regression test, both from the P value (Sig. 0.785) and the calculated F (0.244), both show that there is no significance between schools that have KTR or not and the number of smokers aged 10 - 18 years, P value > α 0.05 and F count < F table (3.47). The implementation of KTR in schools needs to be achieved up to 100% and also in other places where KTR is mandatory because the long-term goal is to reduce the prevalence of the number of smokers.